2020
DOI: 10.1001/jamanetworkopen.2020.6027
|View full text |Cite|
|
Sign up to set email alerts
|

Bupropion for the Treatment of Apathy in Alzheimer Disease

Abstract: IMPORTANCE Apathy is a frequent neuropsychiatric symptom in dementia of Alzheimer type and negatively affects the disease course and patients' and caregivers' quality of life. Effective treatment options are needed. OBJECTIVE To examine the efficacy and safety of the dopamine and noradrenaline reuptake inhibitor bupropion in the treatment of apathy in patients with dementia of Alzheimer type. DESIGN, SETTING, AND PARTICIPANTS This 12-week, multicenter, double-blind, placebocontrolled, randomized clinical trial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 43 publications
0
19
0
Order By: Relevance
“…In the largest RCT using bupropion (150mg per day) -a norepinephrine -dopamine reuptake inhibitor -to treat apathy in 54 nondepressed patients with dementia of the Alzheimer Type (mean MMSE=19.3), the drug failed to improve apathy as measured by the AES-C over a 12 week period when compared with the placebo. 168 Interestingly, secondary analyses focusing on apathy subdomain factors of the AES scale showed significant worsening of the emotional apathy factor in the bupropion group after 12 weeks, whereas no significant differences were found between the groups for the other two factors. 168 Furthermore, the multi-center, placebocontrolled, crossover trial with bupropion 169 for the treatment of apathy diagnosed with the Structured Clinical Interview for Apathy-Dementia in Huntington's dementia failed to reveal significant differences in AES-informant scores between the groups.…”
Section: Treatment and Intervention Efficacymentioning
confidence: 92%
See 1 more Smart Citation
“…In the largest RCT using bupropion (150mg per day) -a norepinephrine -dopamine reuptake inhibitor -to treat apathy in 54 nondepressed patients with dementia of the Alzheimer Type (mean MMSE=19.3), the drug failed to improve apathy as measured by the AES-C over a 12 week period when compared with the placebo. 168 Interestingly, secondary analyses focusing on apathy subdomain factors of the AES scale showed significant worsening of the emotional apathy factor in the bupropion group after 12 weeks, whereas no significant differences were found between the groups for the other two factors. 168 Furthermore, the multi-center, placebocontrolled, crossover trial with bupropion 169 for the treatment of apathy diagnosed with the Structured Clinical Interview for Apathy-Dementia in Huntington's dementia failed to reveal significant differences in AES-informant scores between the groups.…”
Section: Treatment and Intervention Efficacymentioning
confidence: 92%
“…168 Interestingly, secondary analyses focusing on apathy subdomain factors of the AES scale showed significant worsening of the emotional apathy factor in the bupropion group after 12 weeks, whereas no significant differences were found between the groups for the other two factors. 168 Furthermore, the multi-center, placebocontrolled, crossover trial with bupropion 169 for the treatment of apathy diagnosed with the Structured Clinical Interview for Apathy-Dementia in Huntington's dementia failed to reveal significant differences in AES-informant scores between the groups. Summary: There are no established treatments for apathy to date.…”
Section: Treatment and Intervention Efficacymentioning
confidence: 92%
“…Singular positive reports have been published on the use of methylphenidate, istradefylline, MAO inhibitors, yokukansan, and exenatide [ 160 , 161 , 162 , 163 , 164 , 165 ]. Bupropion and choline alphoscerate, a cholinergic precursor, was shown to be effective in treating apathy in other neurodegenerative diseases [ 166 , 167 , 168 ]. A case report of a patient suffering from an auto-activation deficit reported spectacular improvement of symptoms following administration of tricyclic antidepressants [ 169 ].…”
Section: Treatmentmentioning
confidence: 99%
“…In one study, methylphenidate was not effective in enhancing SSRI treatment of apathy in depression [ 23 ]. Another study found that while bupropion was safe, it was not efficacious compared with placebo in the treatment of apathy in patients with Alzheimer’s dementia in the absence of clinically relevant depressed mood [ 24 ]. In Lewy Body Dementia, acetylcholinesterase inhibitors (AchEIs) were found to be useful in a systematic review of four studies [ 12 ].…”
Section: Introductionmentioning
confidence: 99%